Fish oil and multivitamin supplementation reduces oxidative stress but not inflammation in healthy older adults: A randomised controlled trial. (December 2015) - Pipingas, Andrew; Sinclair, Andrew; Croft, Kevin D.; Januszewski, Andrzej S.; Jenkins, Alicia J.; Mori, Trevor A.; Cockerell, Robyn; Grima, Natalie A.; Stough, Con; Scholey, Andrew; Myers, Stephen P.; Sali, Avni; et al.
Abstract: The effects of daily fish oil supplementation, with and without multivitamins, on biochemical markers of health were examined. Healthy adults ( N  = 160) were randomised to receive 3 g of salmon oil with a multivitamin, 6 g of salmon oil with a multivitamin, 6 g of salmon oil in isolation or placebo in a double-blind fashion on a daily basis for 16 weeks. Relative to placebo, both 6 g salmon oil groups displayed significantly lower F2 -isoprostane levels at endpoint. Increases in red blood cell polyunsaturated fatty acids correlated with reductions in F2 -isoprostanes. Treatment had no effect on inflammatory cytokines, C-reactive protein, fibrinogen, cholesterol or triacylglycerol.